IMPLEMENTASI KONSEP KELUARGA SAKINAH, MAWADDAH, WA RAHMAH DALAM DUNIA PENDIDIKAN Studi Analisis Terhadap Siswa SMA Negeri 2 Cibitung - Wafa, Wafaul; Noor, Tajuddin; Wahyudin, Undang Ruslan (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
IMPLEMENTATION OF THE CONCEPT OF FAMILY IN SAKINAH, MAWADDAH, WA RAHMAH IN THE WORLD OF EDUCATION: An Analytical Study of Students of SMA Negeri 2 CibitungThis study seeks to explore the implementation of the ideal family concept in the perspective of Al-Quran Sakinah, mawaddah, wa rahmah in the world of education. Al-Quran is an essential source of life guidelines for mankind to be implemented. The sakinah mawaddah warahmah (samara) family in the perspective of the Qur'an is a picture of a family that is able to provide calm, tranquility, coolness and peace based on faith and piety and can carry out the divine shari'ah of the Rabbi as well as possible. Lately, the ideal family has experienced sharp challenges where the problems are increasing day by day, including increasing divorce cases, the absence of an ideal education concept in educating children, shifting the roles and responsibilities of parents towards earning a living compared to educating the family. This research uses a qualitative approach. The study data were taken using interview, observation and documentation techniques from the students and parents of SMA Negeri 2 Cibitung. Data analysis was carried out using descriptive analytic technique. The results showed that among the strategies to build an ideal family is to build good communication with all family members and be responsible according to their respective roles. In addition, parents are obliged to construct a positive paradigm, one of which is always developing an attitude of gratitude for what they have, not forcing the wishes of those who cannot afford it. In forming a family, it must be based on the Al-Quran and As-Sunnah, one of which is contained in Surat Ar-Ruum verse 21, namely a family that is always peaceful, about and peaceful, and creates an atmosphere of love and affection in the family.